A conceptual replication study of a self-affirmation intervention to improve the academic achievement of low-income pupils in England. Issue 1 (17th February 2022) - See, Beng Huat; Morris, Rebecca; Gorard, Stephen; Siddiqui, Nadia; Easterbrook, Matthew J.; Nieuwenhuis, Marlon; Fox, Kerry; Harris, Peter R.; Banerjee, Robin
ABSTRACT: This paper describes an independently evaluated randomised controlled trial of a self-affirmation intervention, replicating earlier studies, mostly conducted in the US with ethnic minority students. Self-affirmation theory suggests that some stigmatised groups, such as those from ethnic minority or poor families, face stereotype threats which undermine their academic performance. Engaging in value affirmation writing activities when such threats are most salient can give individuals a positive sense of value, negating harmful feelings, and fostering academic learning. The present study, involving 10, 807 pupils aged 14 to 16 in England showed that the intervention can be successfully replicated with children from low socioeconomic backgrounds in England. The analysis showed positive effects for the intervention group. Pupils who completed more exercises also performed better. The findings are worth consideration given that it costs virtually nothing and does no harm.